Politics of Right to Write and Monica Aliâ€™s Fiction - Akhter, University of Rajshahi, Bangladesh, A.F.M. Maswood (Asiatic: IIUM Journal of English Language and Literature, 2014)
The Brick Lane-writer Monica Aliâ€™s status as an ethnic icon â€“ an image so hyped by the white media â€“ automatically curbs her creative freedom of representation and confines her to ghettoes. Consequently, Aliâ€™s other pieces are ignored, not because of their lesser literary merit but for their authorâ€™s treading into â€œnot-permissibleâ€ grounds, that is, â€œnon-ethnicâ€ materials. The audiences back home and within diaspora, on the other hand, tend to consider this Dhaka-born writer just as one more outsider having no legitimacy to deal with them, and they even voiced their outrage in London streets against Brick Lane (2003) for depicting what they considered a â€œshamefulâ€ portrait of them. They question her right to write about â€œhomeâ€ just as the West could not appreciate the European or American settings and characters in her later books. Ali, on her part, however, claims to have disowned these licensing authorities in a bid to safeguard her writerly discretion. Brick Lane thus becomes the metaphor that embodies the poetics and practices of this intricate, intriguing politics in which the hegemonic publishing industry in the West along with the grinding U.S.-U.K. review machine (of The New York Times, The Guardian and so on) has rather a decisive role to play.